Karsinoma Nasofaring dengan Manifestasi Efusi Otitis Media, Emfisema Paru dan Kejang pada Pria Tidak Merokok dengan Pajanan Asap Biomassa - Adji, Iwan Setiawan; Nabilah, Aisyah; Arifinnia, Salwa Ghaisani Syariifah; Hanief, Sekar Mayang Raisa; Rosyita, Fadhilla Jihan; Alghozi, Muhammad Hilmi (FORIKES, 2025)
Nasopharyngeal carcinoma is a head-neck epithelial malignancy with high prevalence in Southeast Asia. Chronic biomass smoke exposure is also potentially carcinogenic. This study aims to document a case of nasopharyngeal carcinoma in a non-smoker setting exposed to chronic biomass smoke, with pulmonary emphysema and a neurological presentation mimicking brain metastases, and to analyze the pathophysiological mechanisms, diagnostic challenges, and clinical and policy implications in areas with high biomass exposure. This study is a hospital case report, involving a single patient. Data were collected from history taking, physical examination, ancillary tests, and treatment outcomes, which were then analyzed descriptively. The study presents a 65-year-old male, a non-smoking farmer from a rural area, who presented with right-sided hearing loss followed by a single seizure. A CT scan revealed a right nasopharyngeal mass extending into the sphenoid and paranasal sinuses with mastoid effusion, and a hypodense lesion in the temporal lobe consistent with an old infarct. A chest X-ray showed pulmonary emphysema, and no brain metastases were found. Discussion: The combination of nasopharyngeal carcinoma and emphysema in a non-smoker suggests a possible etiological link to daily exposure to firewood smoke in an unventilated home. The patient's seizure manifestations are more likely due to metabolic disturbances than metastasis. In conclusion, this case emphasizes the importance of awareness of the risk of nasopharyngeal cancer and lung disease from biomass smoke exposure in a rural non-smoking population, as well as the urgency of environmentally based prevention.Keywords: nasopharyngeal carcinoma; biomass smoke; non-smoker; pulmonary emphysema; seizures ABSTRAK Karsinoma nasofaring merupakan keganasan epitel kepala-leher yang prevalensinya tinggi di Asia Tenggara. Paparan asap biomassa kronik juga berpotensi bersifat karsinogenik. Studi ini bertujuan untuk mendokumentasikan kasus karsinoma nasofaring dengan latar non-smoker yang terpapar asap biomassa kronik, disertai emfisema paru dan presentasi neurologis yang meniru metastasis otak, serta menganalisis mekanisme patofisiologis, tantangan diagnostik, dan implikasi klinis maupun kebijakan di daerah dengan paparan biomassa tinggi. Studi ini merupakan laporan kasus di rumah sakit, yang melibatkan pasien tunggal. Data dikumpulkan dari hasil anamnesis, pemeriksaan fisik, pemeriksaan penunjang, serta hasil terapi, yang selanjutnya dianalisis secara deskriptif. Hasil studi menampilkan seorang pria 65 tahun, petani non-perokok dari daerah pedesaan, datang dengan keluhan penurunan pendengaran kanan, diikuti kejang tunggal. CT-scan menunjukkan massa nasofaring kanan yang meluas ke sinus sphenoid dan paranasal dengan efusi mastoid, serta lesi hipodens di lobus temporalis yang konsisten dengan infark lama. Foto toraks menunjukkan emfisema paru, dan tidak ditemukan metastasis otak. Diskusi: Kombinasi karsinoma nasofaring dan emfisema pada non-perokok menunjukkan kemungkinan hubungan etiologis dengan paparan asap kayu bakar harian di rumah tanpa ventilasi. Manifestasi kejang pasien lebih mungkin akibat gangguan metabolik daripada metastasis. Sebagai kesimpulan, kasus ini menekankan pentingnya kewaspadaan terhadap risiko kanker nasofaring dan penyakit paru akibat paparan asap biomassa pada populasi non-perokok di pedesaan, serta urgensi pencegahan berbasis lingkungan.Kata kunci: karsinoma nasofaring; asap biomassa; non-perokok; emfisema paru; kejang